COVID-19–Related Lung Parenchymal Uptake on 18F-PSMA-1007 PET/CT. (11th December 2021) - Nawwar, Ayah A.; Searle, Julie; Green, Jes S.; Lyburn, Iain D.
Abstract: A 70-year-old man with newly diagnosed prostate cancer underwent 18 F-PSMA-1007 PET/CT for staging. PSMA-avid primary prostatic malignancy was identified. Incidental intense patchy peripheral lung uptake was also noted. The patient tested positive for COVID-19 infection.